Leicester's literary patronage - Woudhuysen, H (1981)
﻿ During the Duke of Alençon's second courtship of Queen Elizabeth the Earl of Leicester emerged as the leading opponent of the marriage. At the same time he began to patronize a circle of writers which included Gabriel Harvey, Edmund Spenser and Philip Sidney, who helped to create the 'golden 1 literature of the English Renaissance. In this thesis I investigate their relations with Leicester and by a detailed examination of their main works, such as the Spenser-Harvey Letters, the Old Arcadia, theShepheardes Calender and theFaerie Queene, and their development, show how they reflect the Earl's intellectual and political concerns. I argue that Alençon was a notable patron and that his growing knowledge of his rival's academic interests encouraged Leicester to maintain his own literary faction. One of his aims was to show the French that English culture was not provincial and he demon- strated this in the entertainment The Four Foster Children of Desire for which he was largely responsible. Having outlined the background of the crisis of the courtship I evoke Leicester's life and circumstances during this period, particularly his relationship with the Queen and patronage at Oxford. I then describe the distinctive interests of his circle in law, history, politics and poetry and go on to establish that Alençon took part in the French academic movement and that his courtiers included distinguished poets and thinkers. The second half of the thesis is a series of detailed studies of Harvey, Spenser and Sidney in relation to Leicester, and their writings during the Alençon court- ship. Finally I examine the court entertainments of this period and argue for the Four Foster Children as a turning-point in Elizabethan literature. My conclusion is that Leicester was a more loyal and discriminating patron than he is usually said to have been and that he played a significant part in introducing the 'golden' age of Elizabethan literature.